A gene missense mutation in diffuse pulmonary lymphangiomatosis with thrombocytopenia: A case report. Issue 39 (25th September 2020) - Zheng, Guixian; Tang, Haijuan; Su, Rui; Liang, Yi; He, Zhiyi; Zhang, Jianquan; Deng, Jingmin; Bai, Jing; Zhong, Xiaoning
Abstract: Introduction: Diffuse pulmonary lymphangiomatosis (DPL) is a rare condition. Most patients with DPL present dyspnea, cough, expectoration, and hemoptysis. There are few reports of DPL accompanied by thrombocytopenia, whose cause remains unknown. Patient concerns: An 18-year-old male patient presented with recurrent cough, expectoration, and dyspnea for 5 years, and thrombocytopenia was observed during a 2-month follow-up. Diagnosis: Chest computed tomography showed diffuse patchy shadows in both lungs, and pleural and pericardial effusions. Immunohistochemical lung tissue staining showed lymphatic and vascular endothelial cells positive for D2-40, CD31 and CD34. Routine blood test revealed platelets at 62 × 10 9 cells/L during follow-up. Bone marrow biopsy was normal. Ultrasound revealed no hepatosplenomegaly. Finally, the patient was diagnosed with DPL accompanied by thrombocytopenia. Interventions: He was treated by subtotal pericardial resection, thoracocentesis, and anti-infective therapy. Oral prednisone was administered for 2 months. Outcomes: The symptoms of cough and shortness of breath were improved, but thrombocytopenia persisted. We investigated the cause of thrombocytopenia. Whole-exome sequencing identified a mutation in exon 3 of the TNFRSF13B gene in this patient. Conclusion: DPL may present with thrombocytopenia and DIC. Patients with thrombocytopenia but not DIC and splenomegaly should be screened for gene mutations.